Peer-to-peer work in the digital meaning society 2050 - Juho Ruotsalainen; Sirkka Heinonen; Joni Karjalainen; Marjukka Parkkinen (Springer, 2022)
The article discusses possible futures of selforganising peer-to-peer work through four transformative scenarios constructed in the Neo-Carbon Energy research project. These futures images probe the futures of work from the perspective of peer-to-peer organisations and distributed renewable energy production. The scenarios lay a systemic view on he development of societies, studying how decentralised renewable energy with low costs could affect society and its social relations. We anticipate the emergence of a digital meaning society, in which the economy is based on the production of meanings and meaningfulness. The article analyses the results of a futures workshop on the futures of work by classifying them to seven core themes. The results of the analysis are compared to related implications for policy-making, and to the Millennium Project Work/Technology Scenarios 2050 for international perspectives. The article presents possible disruptions and key emerging issues, including the novel drivers for inequalities of peer-to-peer work.